MITOL promotes cell survival by degrading Parkin during mitophagy. (10th February 2021) - Shiiba, Isshin; Takeda, Keisuke; Nagashima, Shun; Ito, Naoki; Tokuyama, Takeshi; Yamashita, Shun‐Ichi; Kanki, Tomotake; Komatsu, Toru; Urano, Yasuteru; Fujikawa, Yuuta; Inatome, Ryoko; Yanagi, Shigeru
Abstract: Parkin promotes cell survival by removing damaged mitochondria via mitophagy. However, although some studies have suggested that Parkin induces cell death, the regulatory mechanism underlying the dual role of Parkin remains unknown. Herein, we report that mitochondrial ubiquitin ligase (MITOL/MARCH5) regulates Parkin‐mediated cell death through the FKBP38‐dependent dynamic translocation from the mitochondria to the ER during mitophagy. Mechanistically, MITOL mediates ubiquitination of Parkin at lysine 220 residue, which promotes its proteasomal degradation, and thereby fine‐tunes mitophagy by controlling the quantity of Parkin. Deletion of MITOL leads to accumulation of the phosphorylated active form of Parkin in the ER, resulting in FKBP38 degradation and enhanced cell death. Thus, we have shown that MITOL blocks Parkin‐induced cell death, at least partially, by protecting FKBP38 from Parkin. Our findings unveil the regulation of the dual function of Parkin and provide a novel perspective on the pathogenesis of PD. Synopsis: This study reveals that MITOL is translocated from mitochondria to the ER during the late phase of mitophagy. At the ER, MITOL degrades Parkin, thereby stabilizing FKBP38, and thus promoting cell survival. MITOL mediates ubiquitination of Parkin at lysine 220 residue and promotes its proteasomal degradation. MITOL translocates from mitochondria to the ER in an FKBP38 dependent manner during the late phase of mitophagy. MITOL depletion leads to accumulation of activated Parkin, which in turn degrades FKBP38. Degradation of FKBP38 by Parkin leads to mislocalization of Bcl‐2, calcium leak and cell death. Abstract : This study reveals that MITOL is translocated from mitochondria to the ER during the late phase of mitophagy. At the ER, MITOL degrades Parkin, thereby stabilizing FKBP38, and thus promoting cell survival.